Media Pembelajaran Interaktif Berbasis Augmented Reality untuk Materi Organ Dalam Tubuh Manusia - Raihan, Rafli; Nugroho, Nurhasan; Pratama, Gelard Untirtha (Pusat Riset dan Inovasi Nasional, 2025)
Elementary students’ understanding of human internal organs continues to face challenges due to limited visual media and conventional teaching methods. This study aims to develop an Android-based educational application that integrates Augmented Reality (AR) technology as an alternative solution to introduce internal organs in an interactive and engaging manner. The development model employed is ADDIE, which consists of needs analysis, interface design, application development, implementation, and evaluation stages. The resulting application is capable of displaying 3D marker-based objects accompanied by educational narration and a user-friendly interface. Implementation was conducted at SDN Rancaranji using Unity and Vuforia on Android devices. Evaluation results from 41 respondents, comprising teachers and parents, indicated highly positive responses, particularly regarding the educational value aspect. These findings support the effectiveness of AR technology as an interactive and enjoyable science learning medium aligned with the elementary school curriculum. This study contributes to the development of practical technology-based learning media within the context of Indonesian primary education.